1995
DOI: 10.1063/1.470328
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the (CO)+2 ion by dissociative ionization of argon/carbon monoxide clusters

Abstract: Observation of the lead carbonyls, Pb n CO (n=1-4): Reactions of lead atoms and small clusters with carbon monoxide in solid argon J. Chem. Phys. 122, 034505 (2005); 10.1063/1.1834915 Energy transfer, scattering and dissociation in ion atom collisions: CO 2 + /Ar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The present values are in fair agreement with previous high-resolution VUV photoionization experiments [16] reporting values of 13.05 ± 0.04 eV and 12.91 ± 0.04 eV. Moreover binding energies have been reported to be as high as 1.96 eV (see [17]). The corresponding values derived in the photoionization study are 0.97 ± 0.04 eV and 0.16 ± 0.08 eV, respectively.…”
Section: Electron Impact Ionization Of Carbon Monoxide Clusterssupporting
confidence: 93%
See 1 more Smart Citation
“…The present values are in fair agreement with previous high-resolution VUV photoionization experiments [16] reporting values of 13.05 ± 0.04 eV and 12.91 ± 0.04 eV. Moreover binding energies have been reported to be as high as 1.96 eV (see [17]). The corresponding values derived in the photoionization study are 0.97 ± 0.04 eV and 0.16 ± 0.08 eV, respectively.…”
Section: Electron Impact Ionization Of Carbon Monoxide Clusterssupporting
confidence: 93%
“…The errors given are statistical, and include the errors from the fit to the monomer and cluster signals. It is interesting to note that there exist a number of further experimental results on AE((CO) + 2 ) as summarized by Weitzel and co-workers [17] ranging from 13.15 eV down to 12.73 eV. Using the present ionization energies, the known ionization energy of CO, and the estimated dissociation energy for (CO) 2 and (CO) 3 , the bond energies for CO + − CO and (CO) + 2 − CO are calculated to be 0.83 ± 0.10 eV and 0.22 eV, respectively.…”
Section: Electron Impact Ionization Of Carbon Monoxide Clustersmentioning
confidence: 96%
“…We used a value of 0.13 eV in the present derivation ͑see also below͒ and following the argument above we arrive at an estimate for the dimer ion binding energy of ͑2.55Ϫ0.4 ϩ0.6͒ eV. This is a very high value compared to the bond energy of rare gas atomic clusters or other molecular clusters, 34,35,38 including OClO. Such a large value is, however, not without precedent.…”
Section: D͑oclo-oclomentioning
confidence: 83%
“…Such a large value is, however, not without precedent. Mähnert et al 38 studied the formation of the ͑CO͒ 2 ϩ ion by the dissociation of Ar͑CO͒ 2 clusters in a threshold photoelectron photon coincidence experiment and determined a binding energy of the ͑CO͒ 2 ϩ dimer ion of 1.80 eV from which they suggested that the CO dimer has a trans planar structure. Recently Lauvergnat 39 carried out a sophisticated ab initio SCF calculation to derive the ionization potential of the neutral ozone dimer.…”
Section: D͑oclo-oclomentioning
confidence: 99%
“…Yet, the dissociation energies of the (N2)2 and the (CO)s ion are very different: 1.06 eV for the (N2 )2 ion14 and 1.80 eV for the (CO) ion. 64 The similarity in the dissociation energy of the cluster ions ArCO+, ArN2 , and (N2)+ might be due to a similarity in the bonding situation in these ions , i.e. one which is governed by a charge -induced dipole interaction.…”
Section: Spin and Charge Distribution In Arp And Arco+mentioning
confidence: 99%